Eigene und gemeinsame Lernarbeit Erziehung und Bildung in Verantwortung für eine lebenswerte Zukunft - Schlömerkemper, Jörg (Verlag Barbara Budrich, 2024)
The traditional forms and contents of teaching will no longer meet the challenges of the future. Beyond "educational" knowledge, an expanded and sophisticated understanding of "education" is required. In this objective, an alternative concept of learning organisation is developed: Adolescents develop individual competence profiles in their own learning work and at the same time experience in joint projects that all can and must contribute responsibly to success with their different competences.